REPURCHASE INTENTION DITINJAU DARI STORE ATMOSPHERE, LIFESTYLE, DAN MEDIA SOSIAL (Studi Kasus Pada Kopi Kepi Solo) - Budhi Hartanto; Abdul Halik; Siti Mujanah (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study was to determine the effect of store atmosphere, lifestyle and social media on repurchase intention in Kopi Kepi Solo. This type of research uses descriptive quantitative research. The variables in this study are store atmosphere, lifestyle and social media. The population in this study were all consumers of Kopi Kepi Solo. The sample in this study amounted to 100 people, using purposive sampling technique and data collection using a questionnaire using the coefficient of determination analysis technique, classical assumption test and multiple linear regression. The test results of multiple linear regression analysis show that store atmosphere has a significant effect on repurchase intention, lifestyle has a significant effect on repurchase intention and social media has a significant effect on repurchase intention. Three independent variables explained that store atmosphere, lifestyle and social media had an effect of 71.6% and the rest was influenced by other variables. Keywords: Store Atmosphere, Lifestyle, Social Media